2016
DOI: 10.1186/s13075-016-0963-8
|View full text |Cite
|
Sign up to set email alerts
|

Lymphatic endothelial cells efferent to inflamed joints produce iNOS and inhibit lymphatic vessel contraction and drainage in TNF-induced arthritis in mice

Abstract: BackgroundIn this study, we sought to determine the cellular source of inducible nitric oxide synthase (iNOS) induced in lymphatic endothelial cells (LECs) in response to tumor necrosis factor (TNF), the effects of iNOS on lymphatic smooth muscle cell (LSMC) function and on the development of arthritis in TNF-transgenic (TNF-Tg) mice, and whether iNOS inhibitors improve lymphatic function and reduce joint destruction in inflammatory erosive arthritis.MethodsWe used quantitative polymerase chain reactions, immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
75
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(77 citation statements)
references
References 52 publications
2
75
0
Order By: Relevance
“…Although the PCR experiments on intact lymphatics do not permit us to determine in which cell type the iNOS upregulation occurred, we observed that both lymphatic endothelial and muscle cells in culture exhibited upregulated iNOS mRNA expression following TNF-α treatment (Rehal, Roizes & von der Weid, unpublished data) and we can reasonably infer that both cell types are sensitive to TNF-α and contribute to lymphatic contractile dysfunction by upregulating iNOS expression and NO production. This proposal is further supported by other studies demonstrating iNOS upregulation in cultured lymphatic endothelial cells isolated from sheep, mouse and rat mesenteric lymphatic vessels upon stimulation with LPS, TNF-α, and other cytokines [17,42,45] and in mesenteric lymphatic vessels from old rats, which display an inflamed phenotype[51] Alternatively, NO could also be generated by immune cells reminiscent of macrophages that have recently been reported to populate the wall of mesenteric lymphatic vessels [12,16,40]. Indeed, some of these cells display NF-κB activation (see arrowheads in Fig.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Although the PCR experiments on intact lymphatics do not permit us to determine in which cell type the iNOS upregulation occurred, we observed that both lymphatic endothelial and muscle cells in culture exhibited upregulated iNOS mRNA expression following TNF-α treatment (Rehal, Roizes & von der Weid, unpublished data) and we can reasonably infer that both cell types are sensitive to TNF-α and contribute to lymphatic contractile dysfunction by upregulating iNOS expression and NO production. This proposal is further supported by other studies demonstrating iNOS upregulation in cultured lymphatic endothelial cells isolated from sheep, mouse and rat mesenteric lymphatic vessels upon stimulation with LPS, TNF-α, and other cytokines [17,42,45] and in mesenteric lymphatic vessels from old rats, which display an inflamed phenotype[51] Alternatively, NO could also be generated by immune cells reminiscent of macrophages that have recently been reported to populate the wall of mesenteric lymphatic vessels [12,16,40]. Indeed, some of these cells display NF-κB activation (see arrowheads in Fig.…”
Section: Discussionsupporting
confidence: 78%
“…[38][39][40] While in physiological states this action essentially relies on eNOS, 41,42 several studies demonstrated that NO produced under the catalytic action of iNOS plays a major role in lymphatic dysfunction observed during inflammation. 1,2,43,44 upon stimulation with LPS, TNFα, and other cytokines 26,50,51 and in mesenteric lymphatic vessels from old rats, which display an inflamed phenotype 52 Alternatively, NO could also be generated by immune cells reminiscent of macrophages that have recently been reported to populate the wall of mesenteric lymphatic vessels. 30,53,54 Indeed, some of these cells display NF-κB activation (see arrowheads in Figure 3C).…”
Section: Discussionmentioning
confidence: 99%
“…Nitric oxide synthase (NOS) is a key enzyme in the generation of NO (29). During the development of OA, cartilage cells are impaired, caused by a release of inflammatory factors, which leads to the generation of NO (30). Released NO inhibits cartilage cell proliferation and …”
Section: Discussionmentioning
confidence: 99%
“…This may be related to the high levels of inducible nitric oxide synthase (iNOS) produced by macrophages and LECs. Inducible NOS directly affects lymphatic muscle cells via excess nitric oxide . We observed that in mice carrying the tumor necrosis factor transgene (TNF‐Tg), a model of rheumatoid arthritis (RA), macrophages were attached to LECs in the collecting lymphatic vessel that drains the inflamed joints .…”
Section: Introductionmentioning
confidence: 99%